Detection of butyric spores by different approaches in raw milks from cow, ewe and goat. (January 2023) - Esteban, M.; Díaz, C.; Navarro, J.P.; Pérez, M.D.; Calvo, M.; Mata, L.; Galán-Malo, P.; Sánchez, L.
Abstract: Clostridium tyrobutyricum is described as the main causative agent of late blowing defect in cheese. Currently, there are no fast methods to detect this microorganism in raw milk, which would allow determining the use of milk for fresh or cured cheese. The technique commonly used is the Most Probable Number, which is laborious and non-specific. In this work, we present the optimization of a real-time PCR-based detection method for C. tyrobutyricum spores in raw milk samples. This novel approach extracts DNA in a semi-automatic system with magnetic beads. The applicability of the developed procedure has been tested in field milk samples from cow, ewe and goat (n = 202), allowing detection of low levels of butyric spores. Raw milk samples were also analyzed by microbiological culture in a selective medium for butyric bacteria, and positive colonies were identified by multiplex PCR and 16S rDNA sequencing. Apart from C. tyrobutyricum, other Clostridium spp. were identified, which should be considered for further development of detection methods. Highlights: A method based on qPCR for C. tyrobutyricum spore detection in milk has been set up. The limit of detection is 10 2 spores/mL and it can be performed in about 5 h. The analyzed milk samples presented low levels of C. tyrobutyricum spores.